MAQĀṢID AL-SYARĪ’AH AL-SYĀṬIBĪ DAN AKTUALISASINYA DALAM NILAI-NILAI FALSAFAH PANCASILA - Agustan Ahmad (State Institute of Islamic Studies (IAIN) Palu, 2011)
Allah swt. sent down the syarī’ah to mankind with certain purpose. The purpose of the syarī’ah is to provide benefit to mankind and prevent them from things that are not good. However, the Muslim scholars (ulamā’) have different understanding on the purpose of the syarī’ah and the procedures of its application. Therefore, the problem maqāṣid al-syarī’ah become the object of a separate study in Islamic law. One of the Muslim scholars (ulamā’) who specifically discusses this issue is al-Syāṭibī in his book, al-Muwafaqāt. This article deals with maqāṣid al-syarī’ah of al-Syātibī and its actualization in the philosophy values of Pancasila.